2006
DOI: 10.1089/sur.2006.7.s1-19
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of Surgical Site Infections

Abstract: The need to treat SSIs places a severe financial strain on health care resources. It is possible that treating high-risk surgical patients medically will prove to be more cost-effective than repeated operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
129
1
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(139 citation statements)
references
References 10 publications
0
129
1
6
Order By: Relevance
“…Consequently the cost assigned to developing an SSI is quite low. Other studies have reported median increases in length of stay of several days and consequently assign high costs (exceeding $3,000 in many cases) to SSIs [29,30]. If more severe SSIs requiring longer hospital stays are observed in a larger trial and NPWT proves effective at reducing SSI incidence then the cost-effectiveness results may be more convincing.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently the cost assigned to developing an SSI is quite low. Other studies have reported median increases in length of stay of several days and consequently assign high costs (exceeding $3,000 in many cases) to SSIs [29,30]. If more severe SSIs requiring longer hospital stays are observed in a larger trial and NPWT proves effective at reducing SSI incidence then the cost-effectiveness results may be more convincing.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of undergoing MRSA screening is to facilitate appropriate treatment of colonized patients with intranasal mupirocin and topical chlorhexidine; such treatment has demonstrated success in reducing the number of SSIs and subsequently reduce patient morbidity and hospital costs [10,15,16]. As a result of the limited followup available for patients in our cohort, our study was not able to address the rate of SSIs.…”
Section: Discussionmentioning
confidence: 99%
“…1 A large portion of these costs are attributed to longer hospitalizations, readmissions, and additional surgeries required for the treatment of infected patients. 2 The risk of developing surgical site infections (SSIs) varies tremendously, with orthopedic trauma demonstrating higher rates of SSI than many other surgical specialties. 3,4 However, since orthopedic trauma surgeons are currently reimbursed through a fee-for-service model, there has been little incentive to investigate the costs of treating SSIs among trauma patients.…”
Section: Introductionmentioning
confidence: 99%